THE COMPARISON OF PRINCIPLES OF ROCURONIUM DOSING IN PATIENTS WITH HIGH BODY-WEIGHT INDEX - A. N. Shmakov; N. L. Elizar'eva; A. N. Kolosov; V. N. Kokhno; L. B. Samoylova (Вестник анестезиологии и реаниматологии, 2017)
The quality rates of neuromuscular block with various ways of dosing were compared for the patients with body weight index exceeding 40kg*m-2 who had laparoscopic surgery for gallstone disease. It has been found that dosing per actual body weight did not cause the danger of excessive duration and depths of neuromuscular block, the lowest doses were noted by dosing for ideal weight. The muscle relaxant dose did not deﬁne the development rate and the duration time of the block. The most close direct correlation has been found between the dose and area of body surface therefore the dosing of a muscle relaxant basing on calculation as per 23-33 mg/m2 is more preferable compared to traditional dosing per body weight in case of normal or high body weight index.